THE EFFECT OF HERITAGE NARRATIVE ON READING COMPREHENSION OF SECOND YEAR STUDENTS OF SMP TELEKOMUNIKASI PEKANBARU - Fadila, Husnul; Jismulatif, Jismulatif; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This quasi-experimental research aimed to find out whether there is an effect of heritage narrative on reading comprehension of second year students of SMP Telekomunikasi Pekanbaru. This research was a nonequivalent (pretest and posttest) control-group design. In this design, there two groups as participant (experimental and control group). Heritage narrative was applied in teaching the experimental group while control group was taught by using narrative from other culture. The population of this research was all students of second year students in academic year of 2017/2018. Total number of population was 71. The sample is chosen by using cluster random sampling. In analyzing data, the writer used quantitative approach. The results of the data analysis showed that the mean scores of pre-test were 44.86 (experimental group) and 43.47 (control group). The mean score of students after the treatment were higher than pre-test. Moreover, from the statistical analysis, it was found out the t-test (4.75) was higher than t-table (2.01) at the significance level 5%. It can be concluded that there was effect of heritage narrative on students ’reading comprehension.Key Words: Heritage Narrative, Reading Comprehension.